Teacher Reflections on Assessing Indigenous Cultural Competency in a Criminal Justice Subject Through Interactive Oral Assessment. - Colvin, Emma; Hartley, Jennifer (Journal of Criminal Justice Education, 2026)
Universities in countries with a history of colonisation of First Peoples (e.g. Australia, New Zealand, and Canada) are pivoting to including cultural perspectives and knowledge systems in curricula, supported by a raft of new policies. For criminal justice professions, the legacy of colonisation has shaped justice systems and First Peoples' experiences of justice. Recommendations for the profession to better address these legacies include embedding First Peoples' perspectives and knowledge systems in undergraduate degrees. This paper reports on the development and design of a new assessment of embedded Indigenous content in a criminal justice subject. As experience in developing and deploying an assessment of these skills and knowledge is still relatively new in many institutions, educators may find this paper of interest when developing their assessment.